RETENSI PENGETAHUAN TUMBUHAN PANGAN SUKU REJANG DI KAMPUNG RINDU HATI DALAM KETAHANAN PANGAN - Zikri, Merlian; Hikmat, Agus; Zuhud, Ervizal A. M. (Media Konservasi, 2016)
Development direction of Indonesia's food security today by reviving food diversity by raising the "strength" of local resources and minimize dependence on food imports. Quantitative ethnobotany study approach on the value and benefit requires measurement of the use values of an important traditional food plants and the knowledge level of food etnobologi. The experiment was conducted from February to July 2014 and May 2015 in a tribal society Rejang Rindu Hati Village. Methods of data collection were participant observation and interviews. Analysis of data using an index of important traditional food plant species (Cultural Food Cultivated Significant Index) and index knowledge of ethnobotany in sosiokultur system (Cultural Food Significant Index). The results of the study explained that as many as 199 plant species were identified as food plants, 141 species as cultivation crops and 58 species of wild crops. Cultivation crop were classified into four important crop categories, that were the most important (>383), very important (257-382), somewhat important (131-256) and less important (<130). Wild food plant species belonged to six categories, the most important (>100), very important (50-99), important (20-49), somewhat important (5-19), less important (1-4) and not important (0). While the knowledge level of ethnobotany food plants males larger than females (0,364>0,360), age class V (>69 years) had higher retention of knowledge ethnobotany compared to other age classes because of the experience of life and longevity. It was believed to know all the knowledge ethnobotany of Rejang Tribe. Keywords: plants food, quantitative ethnobotany, rejang, retention